2014
DOI: 10.1186/s13075-014-0432-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in the treatment of traumatic articular cartilage defects: a comprehensive review

Abstract: Articular cartilage has a limited capacity to repair following injury. Early intervention is required to prevent progression of focal traumatic chondral and osteochondral defects to advanced cartilage degeneration and osteoarthritis. Novel cell-based tissue engineering techniques have been proposed with the goal of resurfacing defects with bioengineered tissue that recapitulates the properties of hyaline cartilage and integrates into native tissue. Transplantation of mesenchymal stem cells (MSCs) is a promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(145 citation statements)
references
References 118 publications
(382 reference statements)
1
142
0
2
Order By: Relevance
“…1 BMSCs seeded within biomaterial scaffolds and implanted into focal chondral defects are capable of resurfacing cartilage in animal and human joints, although inconsistent outcomes have been reported based on macroscopic assessment, histological analysis, magnetic resonance imaging, and clinical scoring. [2][3][4][5][6][7] Repair tissue quality has been shown to correlate with functional outcome. [6][7][8] Therefore, tissue-engineering variables, such as cell expansion environment and seeding density of scaffolds, are currently under investigation with the goal of improving neocartilage quality.…”
Section: Introductionmentioning
confidence: 99%
“…1 BMSCs seeded within biomaterial scaffolds and implanted into focal chondral defects are capable of resurfacing cartilage in animal and human joints, although inconsistent outcomes have been reported based on macroscopic assessment, histological analysis, magnetic resonance imaging, and clinical scoring. [2][3][4][5][6][7] Repair tissue quality has been shown to correlate with functional outcome. [6][7][8] Therefore, tissue-engineering variables, such as cell expansion environment and seeding density of scaffolds, are currently under investigation with the goal of improving neocartilage quality.…”
Section: Introductionmentioning
confidence: 99%
“…However, these cells were recently proven to have the ability to differentiate into a different tissue in response to specific signals released by the site of injury, including cartilage injury [51,52]. Adding to animal studies, several authors reported on intra-articular injection of MSCs into the knee for the treatment of cartilage defects and showed good results with regard to pain and clinical outcomes [53][54][55][56]. Injected MSCs were incorporated into the articular cartilage of the injected joint.…”
Section: Intra-articular Bm-msc Injectionmentioning
confidence: 99%
“…In addition, using IGF-1-coupled particles to induce chondrogenic differentiation of BM-MSCs, glycosaminoglycan synthesis was significantly enhanced, compared to BM-MSCs cultured with a single application of soluble IGF-1. The growth factor IGF-1 is known to increase the proliferative capacity of MSCs and also to enhance the synthesis of extracellular matrix proteins [7,15]. The use of particles as a carrier and delivery system seems to improve prolonged availability of IGF-1 within the scaffold, resulting in superior proteoglycan synthesis compared to single application of soluble IGF-1.…”
Section: Discussionmentioning
confidence: 99%